THE EFFECT OF GIVING TOMATO JUICE IN REDUCING CHOLESTEROL LEVELS ON MENOPAUSE IN BPM NURUL UMAIRA TITI PAPAN, MEDAN DELI DISTRICT - Husna Sari; Erlina Hayati; Septa Dwi Insani; Nurul Aini Siagian (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2022)
Cholesterol is a fatty substance in the blood that is needed by the body for the formation of cell walls. Excessive fat can cause coronary heart disease which occurs in the elderly, especially in women who have passed menopause due to a decrease in the activity of the hormones estrogen and progesterone which has an impact on increasing cholesterol levels in the body. One non-pharmacological treatment is to consume tomato juice.This Research Objective To determine the effect of giving tomato juice on reducing cholesterol levels in menopause at BPM Nurul Umaira Titipapan, Medan Deli District. The Research method is a Quasi-experimental design with a pre-post test design. The study was conducted in February-May 2021. The population of this study was menopause who did cholesterol checks at BPM Nurul Umaira Titi papan, Medan Deli District. The sample is 15 people, by Total sampling. The independent variable is menopause, the dependent variable is the cholesterol levels of menopause. The research instrument used an Observation Sheet. Processing of statistical test data Sample T-Test. Research results are showing the difference between pre and post-giving tomato juice obtained an average value of 4.667 with Std. Deviation 41,593 with 95% CI 1,367-28,700. The results of the Independent t-Test to determine the difference in the average value of blood cholesterol levels between the intervention group and the control group obtained a p-value of 0.001 (p<0.05). meaning that there is an effect of giving tomato juice to lower blood cholesterol levels. Conclusion: It can be concluded that tomato juice can help lower blood cholesterol levels in menopause